Teledentistry during COVID-19 - Segura-Gaspar, Paula Lucía (2021)
Objective: To describe the usefulness of teledentistry during the COVID-19 pandemic and how virtualization can benefit dentists and patients. Methods: The bibliographic search will be carried out using the main data sources of international literature on health sciences (MEDLINE) databases up to September 30, 2020 with no language restriction. The information sought will include publications on the benefits in tele-dentistry during the COVID-19 pandemic using the search terms "Teledentistry, COVID-19, Telehealth, and video consultation” Results: Triage will be carried out virtually. Patient data, signs and symptoms of discomfort, medical history, among other variables. will be recorded. Cases of emergency or urgency will be treated in person, while a COVID-19 questionnaire including symptoms, travel history and contact with COVID-19 patients will be given by telephone. Conclusions: Teledentistry is being used for giving advice and to triage patients with symptoms and emergency treatments.